Workshop Asesmen Nasional bagi Guru-Guru Sekolah Dasar Binaan Astra di Takari, Nusa Tenggara Timur - Irna Karlina Sensiana Blegur; Imelda Hendriani Eku Rimo; Patrisius Afrisno Udil; Damianus Dao Samo (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
The challenges of 21st-century learning lead the Indonesian government to make innovations in the education world, one of which is in the learning assessment system. The policy of abolishing the UN and USBN and then proceeding with the implementation of the National Assessment has been carried out since 2020. This is a good policy but teachers and principals' understanding of an assessment system like this still requires assistance. For this reason, this Community Service (PkM) activity was carried out. The PkM team from the Mathematics Education Study Program, Nusa Cendana University collaborated with the Astra Education Foundation – Michael D. Ruslim (YPA-MDR) and four Astra-assisted elementary schools in Takari, NTT, so that there were four principals and thirty-nine teachers who were actively involved in this activity. The Lecture method, question-and-answer, practices, and demonstrations were the methods used. This activity was carried out for three days and went through several stages: preparation, implementation, evaluation-reflection. The results show that this PkM activity has succeeded in achieving the set goals: 1) participants are able to develop Literacy and Numeracy tasks, 2) understand what school activities can be developed as part of implementing the Pancasila student profile and based on nine aspects of the Learning Environment Survey.